A IMPORTÂNCIA DO ALINHAMENTO ENTRE A CULTURA ORGANIZACIONAL E AS POLÍTICAS DE ADMINISTRAÇÃO DE RECURSOS HUMANOS NO ALCANCE DAS METAS ORGANIZACIONAIS ESTUDO DE CASO FUNDAÇÃO FLORESTAN FERNANDES - Ferraz, Claudia Pedreira do Couto (2008)
This work researches the alignment of human resources management practices with the organizational culture and the importance of such alignment in achieving organization s goals and objectives, represented in this study by Fundação Centro de Educação do Trabalhador Florestan Fernandes . In the same way, the study endeavours to understand the practices and presuppositions in a wider context with a continuous iteration with the demands arising from the external environment of the organization. The methodology used in the work is of qualitative character for the possibility that it comprises in treating a strong behavioral and subjective content, in which diversified and hardly controllable factors will interfere, but that allow through description, decodification and translation, reaching a conclusion, not about frequency but about the meaning of certain phenomena of the social world.(AU)